Critical Discourse Analysis of Kamala Harris’s Judgment on Trump’ Handling Over Pandemic In President Election Campaign of the United States 2020 - Abidah, Laelatul (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This research aims to identify the type of judgments and the most judgments were realized in Kamala Harris’s campaign speech on Trump in handling pandemic in president election of United States 2020. The method of this research was using descriptive qualitative research. This research was done by breaking the speech into sentences to find out the Attitude’s judgment and after that identify it. The data were the transcript of Kamala Harris’s campaign speech in the United States President’s election 2020 about Trump’ handling pandemic. Conducting this research, the researcher applied Appraisal Theory by Martin and White (2005). From the analysis, the researcher found there were 160 sentences based on Kamala Harris’s speech about how Trump handling pandemic. From 160 sentences, there were 33 data of judgments, there are 10 data (30,3%) of negative judgment capacity, 15 data (45,4%) of negative judgment tenacity, and 7 data (21,2%) of negative judgment propriety. The percentages showed that the most judgments appear in Kamala Harris speech on Trump’ handling pandemic was about Trump’s negative tenacity.